The effect of an intervention bundle to prevent central venous catheter-related bloodstream infection in a national programme in the Netherlands. (January 2023) - van der Kooi, T.I.I.; Smid, E.A.; Koek, M.B.G.; Geerlings, S.E.; Bode, L.G.M.; Hopmans, T.E.M.; de Greeff, S.C.
Summary: Introduction: Central venous catheters (CVCs) can lead to central line-related bloodstream infections (CRBSIs). A six-item bundle was introduced in 2009 to prevent CRBSI in Dutch hospitals. Aim: This study aimed to determine the impact of an intervention bundle on CRBSI risk. Methods: Data were obtained from hospitals participating in the national CRBSI surveillance between 2009 and 2019. Bundle compliance was evaluated as a total ('overall') bundle (all six items) and as an insertion bundle (four items) and a maintenance bundle (two daily checks). We estimated the impact of the overall and partial bundles, using multi-level Cox regression. Findings: Of the 66 hospitals in the CRBSI surveillance 56 (84.8%) recorded annual bundle (non)compliance for >80% of the CVCs, for one to nine years. In these 56 hospitals CRBSI incidence decreased from 4.0 to 1.6/1000 CVC days. In the intensive care units (ICUs), compliance was not associated with CRBSI risk (hazard ratio (HR) for the overall, insertion and maintenance bundle were 1.14 (95% confidence interval 0.80–1.64), 1.05 (0.56–1.95) and 1.13 (0.79–1.62)), respectively. Outside the ICU the non-significant association of compliance with the overall bundle (HR 1.36 (0.96–1.93)) resulted from opposite effects of the insertion bundle, associated with decreased risk (HR 0.50 (0.30–0.85)) and the maintenance bundle, associated with increased risk (HR 1.68 (1.19–2.36)). Conclusion: Following a national programme to introduce an intervention bundle, CRBSI incidence decreased significantly. In the ICU, bundle compliance was not associated with CRBSI risk, but outside the ICU improved compliance with the insertion bundle resulted in a decreased CRBSI risk.